2009
DOI: 10.1063/1.3126021
|View full text |Cite
|
Sign up to set email alerts
|

A pentacene-based organic thin film memory transistor

Abstract: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-pro t purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 16 publications
1
45
1
Order By: Relevance
“…The colloidal gold nanoparticles were adsorbed onto the amino-terminated self-assembled monolayer surface treated blocking oxide (SiO 2 ) layer and pentacene was used as the channel layer. Mabrook et al reported on similar structured organic transistor-based memory devices, but they used the organic insulator (polymethylmethacrylate (PMMA)) as the gate dielectric layer [54]. Long retention time was reported under a vacuum environment.…”
Section: Mos Field-effect Transistor-type Memory Devicesmentioning
confidence: 98%
“…The colloidal gold nanoparticles were adsorbed onto the amino-terminated self-assembled monolayer surface treated blocking oxide (SiO 2 ) layer and pentacene was used as the channel layer. Mabrook et al reported on similar structured organic transistor-based memory devices, but they used the organic insulator (polymethylmethacrylate (PMMA)) as the gate dielectric layer [54]. Long retention time was reported under a vacuum environment.…”
Section: Mos Field-effect Transistor-type Memory Devicesmentioning
confidence: 98%
“…Not surprisingly, then, many different types of organic memory devices have also been reported e.g. switchable resistive memory [11,12], floating gate memory devices [13] and memory transistors [14]. Also reported are organic versions of dynamic [15] and static [16][17][18][19] random access memory i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Not only device structures and discrete devices are widely studied [1,2], but logic arrays are developed either [3,4].…”
Section: Introductionmentioning
confidence: 99%